Extraction and Characterisation of Dioclea reflexa Hook. F. Seed Oil: Extraction of Dioclea reflexa Seed Oil (Biological Sciences - PJSIR, 2010)
Physicochemical analysis of the oil of Dioclea reflexa Hook f. seeds revealed the acid value, saponification value, iodine value, ester value and iodine number of the seeds to be 8.69 mg KOH/g, 251 mg KOH/g, 72.8 mg I/g, 242 and 27.9, respectively. The fatty acid composition determined by gas chromatography (GC) showed individual unsaturated fatty acid to be oleic acid (18:1), 0.8%, while the saturated fatty acids were palmitic acid (16:0), 10.2% and stearic acid (18:0), 21.9%. The infrared spectroscopy (IR) of the oil was also undertaken. The high saponification and iodine values of D. reflexa oil suggest its possible utilization in alkyd resin, shoe polish, liquid soap and shampoo production.